Analisis Hidrologi Model Soil Moisture Accounting Menggunakan Program HEC-HMS Untuk 1 Tahun Kalibrasi (Studi Kasus: DAS Rokan Hulu AWLR Lubuk Bendahara) - Nadhella Ghaifany; Yohanna Lilis Handayani; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The availability of water is very important in our life and the other organisms. Use of water is important for daily activities such as household necessities, irrigation, industry, and other activities. In this research, the location isin Rokan Kiri sub-watershed at Lubuk Bendahara Station. The development of the life in Rokan Hulu Regency need repairs and the provision of facilities and infrastructure, including the availability of water. The need forwater will increase from year to year along with developments in various sectors, the agricultural sector, and increasing number of human populations which cause crises and lack or scarcity of water. This situationcertainly making people difficulty to fulfill daily needs. To avoid problems in the future, it is necessary to longterm debt forecasting with one of the methods that can be used, namely Soil Moisture Accounting method, in the HEC-HMS program with some required data, such as rain data, discharge data and climatological data with a one year data period, thai is 2007, where these parameters are inputted to carry out the calibration and verification process that get the most optimal results and close to the results of observations. Based on thisresearch, it can be concluded that the value of the Percent error in discharge volume for one year of calibration is the PEV results for the calibration process results of 4.27%